Lipid releasing characteristics of microalgae species through continuous ultrasonication - Natarajan, Ramya (2015)
In this study, the lipid releasing characteristics of several microalgae species through continuous ultrasonication was examined. Two marine microalgae species, Tetraselmis suecica and Nannochloropsis sp., and one freshwater species, Chlorella sp. were ultrasonicated directly after cultivation. The cell disruption efficiency and lipids releasing pattern from microalgae cells were measured under various ultrasonication conditions. It was found that cell disruption efficiency correlates well with ultrasonication energy consumption despite the ultrasonication conditions. Lipids in Chlorella sp. that has rigid cell walls were released to the aqueous phase after cell disruption. Tetraselmis suecica and Nannochloropsis sp. that have flexible cell membranes tend to coil up and retain the membrane lipids after disruption. Continuous ultrasonication can be a potential method to release the lipids in rigid walled microalgae species without expensive dewatering steps.